ANALISIS KONSEP CUSTOMER VALUE DALAM STRATEGI PEMASARAN - Putra, Albertus Dimas Aji; Beyah, Alain Vincent; Himawan, Andi Yunita; Millati, Ashfi; Zainulmala, Amin; Rohendi, Acep (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2026)
In an increasingly competitive business environment, creating and delivering superior customer value has become a critical foundation for achieving sustainable competitive advantage. This systematic literature review aims to synthesize conceptual and empirical developments regarding the relationship between customer value and marketing strategy. Based on an analysis of selected literature, the findings reveal that customer value is a multidimensional construct encompassing subjective-perceptual (physical, emotional, intellectual, spiritual) and objective-economic (Customer Lifetime Value) aspects. The Customer Value Proposition (CVP) serves as the strategic core that bridges internal capabilities with market expectations. The effective implementation of marketing strategy—primarily through product and price mix—empirically proves to translate value promises into customer satisfaction, which subsequently drives financial performance and shareholder value. These findings underscore the importance of a value-centric marketing approach, supported by precise segmentation and data-driven personalization, for building long-term business resilience. Keywords: Customer Value, Marketing Strategy, Customer Lifetime Value (CLV), Value Proposition, Segmentation, Competitive Advantage.